2021
DOI: 10.1186/s13034-021-00384-4
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ experiences of the information they received about the coronavirus (Covid-19) in Norway: a cross-sectional study

Abstract: Background In the first months of the coronavirus (Covid-19) pandemic, many countries took radical prevention measures. Authorities had to communicate with the public regularly to explain and ensure compliance with these measures and promote safety. The information given by authorities was mainly developed for adults, but children and adolescents may have different needs when it comes to information. This study examined how adolescents perceived information about Covid-19 provided by the media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
6
11
1
2
Order By: Relevance
“…23 The present data also confirm the results of a survey among Norwegian adolescents during the first wave, in which almost half (49%) were satisfied or very satisfied with the information provided about COVID-19, 12% were dissatisfied or very dissatisfied, and 39% were neither satisfied nor dissatisfied. 24 The majority (52%) were not concerned about becoming infected with COVID-19. 24 In another study among adolescents during the first wave in an urban area of Norway, only 7% worried about becoming infected, while 53% worried about infection among their family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The present data also confirm the results of a survey among Norwegian adolescents during the first wave, in which almost half (49%) were satisfied or very satisfied with the information provided about COVID-19, 12% were dissatisfied or very dissatisfied, and 39% were neither satisfied nor dissatisfied. 24 The majority (52%) were not concerned about becoming infected with COVID-19. 24 In another study among adolescents during the first wave in an urban area of Norway, only 7% worried about becoming infected, while 53% worried about infection among their family members.…”
Section: Discussionmentioning
confidence: 99%
“… 24 The majority (52%) were not concerned about becoming infected with COVID-19. 24 In another study among adolescents during the first wave in an urban area of Norway, only 7% worried about becoming infected, while 53% worried about infection among their family members. 25 The Norwegian strategy aims to be based on transparency, and in this context, confidence is earned through openness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study conducted under boys and girls in Norway revealed that girls are more affected by the pandemic and more concerned to become infected with the SARS-COV-2 virus than boys. 14 Also Zhou et al found that in Chinese adolescents girls were at higher risk for depressive and anxiety symptoms during the pandemic. 15 Further underpinned by results from Schmidt et al revealing female gender as a main factor to be more affected.…”
Section: Discussionmentioning
confidence: 99%
“…The indicated gender-differences in being adversely affected by the pandemic, especially the possible detrimental effects on girl's mental health are strengthened by other findings. For example, a study conducted under boys and girls in Norway revealed that girls are mentally more affected by the pandemic and more concerned to become infected with the SARS-COV-2 virus than boys [14]. Also Zhou et al found that in Chinese adolescents girls were at higher risk for depressive and anxiety symptoms during the pandemic [15].…”
Section: Gender Differencesmentioning
confidence: 99%